Modelagem da capacidade de suporte da Laguna de Saquarema RJ após a abertura de uma conexão permanente com o mar - Carloni, Flávia Beatriz Beserra Azevedo (2005)
Saquarema municipality has been subject to a slower urbanization and a less advanced degradation in comparison to other regions of the Região das Baixadas Litorâneas. Nevertheless, its lagoonal system has been threatened by uncontrolled urban expansion leading to an accelerated closure of its natural sand bar. The solution proposed by the SERLA foundation was the construction of a groin and the channel dredging, that was finished in the beginning of 2003. The objective of this work was the evaluation of the water quality changes due to the bar opening and, through a numerical model, simulate the impact of the population growth and determine the ecosystem support capacity. For that, a mass balance through the system modeling was carried out, focusing on the principal cause of eutrophication, the nutrients (N and P) and de population density of the city. Sampling was made together with the Consórcio Intermunicipal Lagos-São João. The nutrient budget was obtained through a compartmented input/output model and the population projections were obtained through the methodology utilized by IBGE. Simulations were performed for the years 2000, 2010, 2020, 2030, 2040 and 2050. In the first simulated scenario the considered effluent load of the city corresponded to the permanent population and in the second one pertained to the permanent population plus the floating population, that means the vacationers population. The mathematical model utilized here was satisfactory and permitted the general analysis of the system support capacity. The predictions showed that the permanent bar opening will not be enough to solve the eutrophication problem if the nutrients loading to the system does not get reduced, through land reclamation control or through the implementation of an efficient treatment system or both of them.